Piano lessons can be murder - Stine, R. L. (New York, NY : Scholastic, 1993)
Convinced that there is something creepy about his new piano teacher, Jerry soon hears terrifying stories about Dr. Shreek's music school and students who never completed their lessons alive.
"An Apple paperback."
530
530
Accelerated Reader AR
Keywords: Piano -- Study and teaching -- Juvenile fiction; Ghosts stories; Teachers -- Juvenile fiction